Registration of LCS ‘Valiant’ hard red winter wheat - Baenziger, P. S.; Masterson, S. D.; Boehm, J. D.; Belamkar, V.; Barnett, M. D.; Rose, D. J.; Xu, L.; Wegulo, S. N.; Regassa, T.; Easterly, A. C.; Creech, C. F.; Santra, D. K.; et al. (Journal of plant registrations, 2023)
Historically cultivars developed jointly by the University of Nebraska‐Lincoln and USDA‐ARS wheat (Triticum aestivum L.) improvement project tend to be late and better adapted to the northern Great Plains. LCS ‘Valiant’ (Reg. no. CV‐1196, PI 693223; tested as NE10478‐1) was released based on the merits of its earliness, agronomic performance, relevant disease resistances, and end‐use quality characteristics and its adaptation to the central Great Plains. As such, the line was licensed to Limagrain Cereal Seeds for their ability to market outside of Nebraska. LCS Valiant hard red winter wheat was released in March 2020 by the developing institutions and the licensee. NE10478‐1 was a selection in 2011 for uniformity and grain yield from NE10478, which was derived from the cross NI03418/‘Camelot’. The pedigree of NI03418 is W91‐248/NE95544 (=McVey 78015/NE88521)//‘Thunderbird’. The final cross of NE10478 was made in 2004. The F1 generation was grown in Yuma, AZ, in 2005, and the F2 to F3 generations were advanced as bulks at Mead, NE, in 2006–2007 or sent for Hessian fly resistance screening by the USDA. In 2007, single F3‐derived F4 rows were planted for selection. There was no further selection in NE10478 other than to remove off‐types thereafter until 2011 when heads were selected to increase uniformity. LCS Valiant was evaluated in replicated trials thereafter. It has excellent winter survival, acceptable reactions to many of the common diseases in its target area, and good end‐use quality for bread making. Core Ideas Valiant is an early hard red winter wheat adapted to the central Great Plains for dryland production. Valiant has excellent winter survival and stem rust resistance and good Hessian fly resistance. The end‐use quality for bread making of Valiant is very good.